Abnormal resting-state functional connectivity of the nucleus accumbens in multi-year abstinent heroin addicts - Zou, Feng; Wu, Xinhuai; Zhai, Tianye; Lei, Yu; Shao, Yongcong; Jin, Xiao; Tan, Shuwen; Wu, Bing; Wang, Lubin; Yang, Zheng (Journal of neuroscience research, 2015)
Functional neuroimaging studies suggest that abnormal brain functional connectivity may be the neural underpinning of addiction to illicit drugs and of relapse after successful cessation therapy. Aberrant brain networks have been demonstrated in addicted patients and in newly abstinent addicts. However, it is not known whether abnormal brain connectivity patterns persist after prolonged abstinence. In this cross‐sectional study, whole‐brain resting‐state functional magnetic resonance images (8 min) were collected from 30 heroin‐addicted individuals after a long period of abstinence (more than 3 years) and from 30 healthy controls. We first examined the group differences in the resting‐state functional connectivity of the nucleus accumbens (NAc), a brain region implicated in relapse‐related processes, including craving and reactivity to stress following acute and protracted withdrawal from heroin. We then examined the relation between the duration of abstinence and the altered NAc functional connectivity in the heroin group. We found that, compared with controls, heroin‐dependent participants exhibited significantly greater functional connectivity between the right ventromedial prefrontal cortex and the NAc and weaker functional connectivity between the NAc and the left putamen, left precuneus, and supplementary motor area. However, with longer abstinence time, the strength of NAc functional connectivity with the left putamen increased. These results indicate that dysfunction of the NAc functional network is still present in long‐term‐abstinent heroin‐dependent individuals. © 2015 Wiley Periodicals, Inc. Heroin addicts still exhibited aberrant NAc functional connectivity even after more than 3 years abstinence from drug use. However, some impaired connectivity was gradually recovered with increasing durations of abstinence.